Implementasi Inovasi Program Multiple Intelligences Research (MIR) di Sekolah Dasar Inklusi Ponorogo - Karisma, Linda Ayu; Ngadhimah, Mambaul; Qholik, Wisnu (Southeast Asian Journal of Islamic Education Management, 2024)
The educational tendency in Indonesia to equalize intelligence standards between students through formal tests can kill students' potential intelligence, interests and talents. Minimal awareness of the concept of multiple intelligences (multiple intelligences) educational institutions in Indonesia need more innovative solutions so that efforts to improve the quality of education can be more optimized. The MIR program innovation initiated by Munif Chatib is the right solution so that the concept of different student intelligence can be understood and appreciated as a basis for determining methods and styles in learning activities. The research method used in this research is descriptive qualitative research with a case study type of research (case study). The data collection technique used is an in-depth interview (indepth interview), participatory observation and documentation processed using Miles, Huberman and Saldana's interactive model data analysis technique which consists of four stages in the form of data collection, data condensation, data presentation and data verification. The location of this research was carried out at SD Immersion Ponorogo as a school with branding inclusion. This research aims to analyze the process of spreading MIR program innovation so that it can become a new breakthrough in the world of education to better appreciate and develop students' various intelligences. The research results show that the process of spreading innovation is carried out in line with Everett M Roger's theory of innovation diffusion which consists of innovation, communication channels, time period and social systems as an effective and efficient dissemination strategy. The MIR program is used as a reference for teachers in determining students' learning styles and models at Immersion Elementary School according to their multiple intelligences more effectively and efficiently. The learning styles used include: storry telling, brainstorming, tape recording, journal writing, fieldtrip, and project based learning.